FAKTOR PEMICU KONFLIK PERTANAHAN (Studi Kasus: Konflik Tanah Antara Masyarakat Desa Muara Dilam dengan PT Citra Sardela Abadi pada tahun 2012) - Widiani, Nice; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The society of Muara Dilam, Village Kunto Darussalam District, Rokan Hulu are one of costumary society that have land conflict. In this case, actually the society have land right and ather same right in using the land in their area for their prosperity through together agreement of this costumry society. In fact, the land righ was always be conflict, generally in our country, include at Muara Dilam Village. There fore, this study has purposed to find out, what are the trigger factors of land matter, between the society of Muara Dilam Village and PT Citra Sardela Abadi in 2012. The research methodology was qualitative research, and for the data used primary and secondary data. These data were got from main informen and additional informen. Data collection Technique was used interviewing and documentating.Than it analyzed by giving description about research result. From the research was found characteristic conflict issue. It was began because Establiment Palm Oil Platation that took up some society land. Unclarity of Paying also was one of the main factor in making land conflict between the society Muara Dilam Village and PT Citra Sardela Abadi. This conflict also happened because of involving individual conflict, it was the social and economy disprepancy between the society Muara Dilam Village and PT Citra Sardela Abadi. The Situational conflict was about the lacking involving the Muara Dilam Village society, and this conflict didnt involve regional goverment and Badan Pertanahan Nasional get, also some opinion said because the lack epordination of Rokan Hulu government toward the society.Key words : Trigger Factor Matter, Characteristic Conflict Issue, Involving Individual Conflict, and Situasional.